2018
DOI: 10.1111/are.13857
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon and nitrogen ratio (C:N) manipulation on the production performance and immunity of Pacific white shrimpLitopenaeus vannamei(Boone, 1931) in a biofloc‐based rearing system

Abstract: A 16-week indoor culture trial was conducted to evaluate the effect of varying C:N ratio on growth performance, physico-chemical parameters, microbial dynamics, feed utilization, and immunological parameters. The experiment comprised of five biofloc treatment groups (with varying C:N ratio 5:1, 10:1, 15:1, 20:1) and a control with three replicates each, having 100 nos/m 3 as stocking density in 500 L tanks with constant aeration. The C:N ratios of the treatments were manipulated using molasses as an organic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
54
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 68 publications
8
54
2
Order By: Relevance
“…In this study, total C and N input and C:N input were similar in all tanks. But other studies show more water column flocculated matter develops at increasing total C input and increasing C:N system input up to 20, while shrimp protein retention shows an optimum at C:N system input of 15 (Panigrahi et al, 2019). The C:N input in this experiment was 10 for all tanks, which is not high.…”
Section: Figure 6 Reconstructed Distributi On Of Protein Accumulati contrasting
confidence: 59%
See 1 more Smart Citation
“…In this study, total C and N input and C:N input were similar in all tanks. But other studies show more water column flocculated matter develops at increasing total C input and increasing C:N system input up to 20, while shrimp protein retention shows an optimum at C:N system input of 15 (Panigrahi et al, 2019). The C:N input in this experiment was 10 for all tanks, which is not high.…”
Section: Figure 6 Reconstructed Distributi On Of Protein Accumulati contrasting
confidence: 59%
“…In consequence, a well-balanced food web will develop, delivering natural food to the culture animal. Developing such a lower-cost and more ecological-based production system has been given more and more attention in research (Joffre and Verdegem, 2019, Hari et al, 2004, Panigrahi et al, 2019, Anand et al, 2015, Panigrahi et al, 2018. Natural food, such as biofloc and periphyton, are known to contribute additional energy and protein to the diet of shrimp in ponds (Chapter 4, De Schryver et al, 2008, Avnimelech, 2009, Wasielesky Jr et al, 2006, Asaduzzaman et al, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in a negative growth rate. Many studies have shown that growing of shrimp species such as L. vannamei in biofloc system can improve shrimp growth as compared to clear water (Khanjani et al, 2016 andPanigrahi et al, 2018). Also, the results indicated that the abnormalities found in shrimp fed with biofloc with corn flour as carbon source possibly correspond with the shrimp cannibalistic behavior.…”
Section: Growth Performance and Feed Utilizationmentioning
confidence: 93%
“…In order to provide a carbon source for heterotrophic bacteria, carbohydrate can be directly added to the cultured water or incorporated into the artificial feed. To promote the bacterial growth, carbohydrate addition is carried out to adjust the C/N ratio of the system to 10 or more (Azim et al, 2007; Cavalli, and Wasielesky, 2012and Panigrahi et al, 2018. The availability of carbon thus allows more efficient use of nitrogen as the excreted nitrogen will be converted in bacterial biomass, which is further consumed by the cultured species.…”
mentioning
confidence: 99%
“…These two aspects (C:N ratio and probiotics) should mediate the effects of biofloc technology on the growth of shrimp (Panigrahi et al. 2018a, 2018b; Hostins et al. ).…”
mentioning
confidence: 99%